PTH-020 Too Old to Push? A Prospective Comparison Study on The Safety of Double Balloon Enteroscopy with Propofol Versus Standard Sedation in The Elderly. (17th August 2016) - Ching, H-L; Branchi, F; Sanders, DS; Turnbull, D; Sidhu, R
Abstract : Introduction: Propofol sedation is increasingly being used for complex endoscopy. Double balloon enteroscopy (DBE) has been shown to be poorly tolerated using standard sedation. We investigated the feasibility and safety of DBE in the elderly compared to the young, using propofol versus standard sedation in our routine small bowel service. Methods: Between March 2013 and December 2015, all patients undergoing DBE were prospectively recruited. Standard sedation with fentanyl and midazolam or anaesthetist-assisted propofol sedation was decided based on patient history and the expected complexity of procedure. Patients were categorised by age into elderly: ≥70 years and young: <70 years and the type of sedation used. Patient data from the four cohorts were collected and compared including hospital and anxiety and depression scores (HADS). Pain, discomfort and distress scores were measured post-DBE. Results: A total of 183 patients underwent DBE. Ten elderly patients (50% male, 80% oral) and 72 young patients (43% male, 79% oral) received propofol respectively whilst 25 elderly patients (44% male, 80% oral) and 76 young patients (51% male, 83% oral) received standard sedation. Background demographics, comorbidities and HADS were comparable. There was no difference in the mean dose of propofol used in elderly or young patients (mean 1032 mg vs 1097 mg, p = 0.651) or the procedure time in any group (p = 0.081). The most common indications for DBE were iron deficiency anaemia (57.1%), overt gastrointestinal bleeding (20%) and suspected Crohn's disease (11.4%) in elderly patients; akin to that in young patients (31.8%, 7.4%, 23.6% respectively). The most common findings at DBE (elderly vs young) were angioectasias (37.1% vs 18.9%, p = 0.025), tumours/masses (17.1% vs 17.6%, p = 1), ulcers (17.1% vs 13.5%, p = 0.593) and a normal examination (22.9% vs 39.2%, p = 0.080). Diagnostic and therapeutic yields were also comparable in all groups (range 60–90%, p = 0.205 and 24–50%, p = 0.054 respectively). There were no complications in elderly patients receiving propofol. One elderly patient receiving standard sedation had a significant troponin rise. Propofol gave lower patient pain, discomfort and distress scores compared to sedation (p < 0.05). Conclusion: This is the first study to compare sedation types for DBE in the elderly. Our data suggests that not only is safety comparable in the elderly receiving propofol compared to standard sedation during DBE but tolerability is significantly better. This would support the use of propofol sedation for DBE in elderly patients. Disclosure of Interest: None Declared